2022
DOI: 10.1002/ar.24932
|View full text |Cite
|
Sign up to set email alerts
|

Paratympanic sinuses in juvenile Alligator

Abstract: Crocodylia has an extensive epithelial pneumatic space in the middle ear, paratympanic sinus system. Although fossil and extant crocodylian paratympanic sinus systems have been studied recently using the computed tomography (CT) and three‐dimensional (3D) reconstruction data, due to the soft tissue nature of the pneumatic system and presence of its surrounding soft tissue structures, some boundaries, and definitions of each extension remain ambiguous. We describe the comprehensive paratympanic sinus system in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 97 publications
(323 reference statements)
0
3
0
Order By: Relevance
“…Another obvious benefit is that a specimen may be used in different projects by multiple researchers at any given time. For example, during a 3-year period (2020–2022), more than 43 unique users downloaded the same data set of a gharial skull ( Gavialis gangeticus ; UF: Herp:118,998; https://doi.org/10.17602/M2/M39794 ), resulting in at least 10 publications from authors in seven countries (Hone et al 2020 , Bowman et al 2021 , Cowgill et al 2021 , 2022 , Pochat-Cottilloux et al 2021 , Serrano-Martínez et al 2021 , Iijima et al 2022 , Schwab et al 2022 a, 2022b, Tahara and Larsson 2022 ). These digital data grow the number of researchers able to interact with specimens, especially people from Low and Middle Income Countries lacking local collections or the resources to travel to other collections.…”
Section: Communities Benefiting From Overt Datamentioning
confidence: 99%
“…Another obvious benefit is that a specimen may be used in different projects by multiple researchers at any given time. For example, during a 3-year period (2020–2022), more than 43 unique users downloaded the same data set of a gharial skull ( Gavialis gangeticus ; UF: Herp:118,998; https://doi.org/10.17602/M2/M39794 ), resulting in at least 10 publications from authors in seven countries (Hone et al 2020 , Bowman et al 2021 , Cowgill et al 2021 , 2022 , Pochat-Cottilloux et al 2021 , Serrano-Martínez et al 2021 , Iijima et al 2022 , Schwab et al 2022 a, 2022b, Tahara and Larsson 2022 ). These digital data grow the number of researchers able to interact with specimens, especially people from Low and Middle Income Countries lacking local collections or the resources to travel to other collections.…”
Section: Communities Benefiting From Overt Datamentioning
confidence: 99%
“…In V. robustus it is ellipsoidal in shape, has a mean height of 3.2 mm, and 6.2 mm in anteroposterior length. The fenestra ovalis communicates with the stipedial diverticulum of the middle ear (StiPR, Figure 11a,c; Tahara & Larsson, 2022). The perilymphatic foramen lies posteroventrally to the fenestra ovalis ; it links the endosseous labyrinth to the extracapsular portion of the perilymphatic sac (Kuzmin et al, 2021).…”
Section: Neuroanatomical and Pneumatic Descriptionmentioning
confidence: 99%
“…Earlier studies have examined the earflaps; testing for possible acoustic filtering (Wever & Vernon, 1957) or alteration of the impedance matching by trapping air bubbles (Higgs et al, 2002), but no significant auditory role has been found. The middle ear cavities of crocodilians are linked by dorsal and paired ventral paratympanic passages (e.g., Dufeau & Witmer, 2015; Tahara & Larsson, 2022). The ventral paratympanic passages open into the pharynx through a muscular valve (Owen, 1850); examination suggests that this valve does not play an auditory function (Young & Bierman, 2019).…”
Section: Introductionmentioning
confidence: 99%